2014
DOI: 10.1186/1746-6148-10-67
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma lipoprotein profiles and malondialdehyde between hyperlipidemia dogs with/without treatment

Abstract: BackgroundThe aim of this study is to compare metabolic parameters, malondialdehyde as a lipid oxidation marker, and lipid profiles between dogs with untreated hyperlipidemia and hyperlipidemia with treatment, in order to examine the usefulness of malondialdehyde and lipid profiles as diagnostic parameters at early stages of hyperlipidemia.ResultsDog samples were collected from four different veterinary clinics across Japan from March to June 2013. They were separated into three groups: control, untreated hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Interestingly a similar effect was not observed in group C, thus letting us hypothesize an additional beneficial effect of PMPA. An increase in serum total cholesterol and/or triglyceride concentrations are indicative of diseases associated with endocrine disorders (hypothyroidism, hyperadrenocorticism, diabetes mellitus), obesity, protein‐losing nephropathy, pancreatitis, and liver disease (De Marco et al., 2017; Li et al., 2014; Sato et al., 2018). Hyperlipidemia in dogs has been associated with several clinical complications such as insulin resistance, increased liver enzyme activity, gallbladder mucocele, behavioural changes, peripheral neuropathies, and seizures (De Marco et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly a similar effect was not observed in group C, thus letting us hypothesize an additional beneficial effect of PMPA. An increase in serum total cholesterol and/or triglyceride concentrations are indicative of diseases associated with endocrine disorders (hypothyroidism, hyperadrenocorticism, diabetes mellitus), obesity, protein‐losing nephropathy, pancreatitis, and liver disease (De Marco et al., 2017; Li et al., 2014; Sato et al., 2018). Hyperlipidemia in dogs has been associated with several clinical complications such as insulin resistance, increased liver enzyme activity, gallbladder mucocele, behavioural changes, peripheral neuropathies, and seizures (De Marco et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia in dogs has been associated with several clinical complications such as insulin resistance, increased liver enzyme activity, gallbladder mucocele, behavioural changes, peripheral neuropathies, and seizures (De Marco et al., 2017). The fibrates are currently considered the most effective antihyperlipidemic drugs available, whereas the statins are a class of LDL‐cholesterol lowering drugs (Li et al., 2014). Mefepronic acid in the present investigation produced a significant decrease in cholesterol concentrations over time, while triglycerides, after a first reduction from T0 to T2, showed a tendency to increase again at T3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that antioxidant levels increase due to increased oxidative stress during the development of obesity (Sabitha et al, 2014). Previous studies determined higher bilirubin levels in obese or hyperlipidemic dogs and humans (Yamka et al, 2006;Li et al, 2014;Piantedosi et al, 2016;Bosco et al, 2018). The bilirubin level determined in obesity increases to reduce the increasing oxidative stress load in metabolism and creates an antioxidant effect (Zhong et al, 2017).…”
Section: Hematologic and Biochemical Profilesmentioning
confidence: 98%
“…MDA is a product of lipid peroxidation reaction and MDA levels increase in parallel with increased oxidative stress in obesity (Holguin and Fitzpatrick, 2010;Tabakoglu and Durgut, 2013;Amirkhizi et al, 2010). In a study conducted on dogs with hyperlipidemia, serum MDA levels were measured before and after treatment and it was determined that the MDA level decreased after treatment (Li et al, 2014). In another study by Kawasumi et al (2018), MDA levels were found to increase, although not statistically, in obese dogs fed high-fat diets for a long period.…”
Section: Hematologic and Biochemical Profilesmentioning
confidence: 99%
“…Meanwhile, hyperlipidemia can affect the brain and kidney (Cabrera, Artacho, & Giménez, 2006; Furrow et al, 2016). However, many hyperlipidemia canines do not show obvious symptoms which makes hyperlipidemia difficult to be diagnosed (Li et al, 2014). Of great importance is hyperlipidemia with insignificant symptoms and potential complications, it is necessary to find an effective method to decrease serum TG and CHO.…”
Section: Introductionmentioning
confidence: 99%